Relationship between socio-economic variables and preference towards herbal-based products: the Malay experience - Kamarulzaman, Nitty Hirawaty; K. N. Vaiappuri, Selvakkumar; Samdin, Zaiton; Imran, Siti Nasihah (International Society for Southeast Asian Agricultural Sciences, 2013)
Herbal-based products are getting popular in Malaysia especially among Malays due to their claimed benefits. However, some Malay consumers prefer not to consume herbal-based products for many reasons. The objective of this study is to determine consumers' perception towards herbal-based products as an alternative medicine. A total of 150 Malay respondents were selected to take part in this study. Face-to-face interviews using a structured questionnaire were carried out to get responses among the respondents in the Klang Valley, Malaysia. The results revealed that Eurycoma longifolia Jack (Tongkat Ali) was the most preferred herb among the majority followed by Orthosiphon aristatus (Misai Kuching), Labisia pumila (Kacip Fatimah) and Centella asiatica (Pegaga). Ficus deltoidea (Mas Cotek) was the least preferred herb among the respondents in this study. Most of the herbal-based products were consumed as a source of energy, for health and fitness, to cure sickness and disease and for enhancing beauty. This study provides some information on the perception towards herbal-based products consumption among Malay consumers.